2022
DOI: 10.1002/jmv.27976
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of ACE2 and TMPRSS2 coding variants as a risk factor for SARS‐CoV‐2 from 946 whole‐exome sequencing data in the Turkish population

Abstract: Heterogeneity in symptoms associated with COVID‐19 in infected patients remains unclear. ACE2 and TMPRSS2 gene variants are considered possible risk factors for COVID‐19. In this study, a retrospective comparative genome analysis of the ACE2 and TMPRSS2 variants from 946 whole‐exome sequencing data was conducted. Allele frequencies of all variants were calculated and filtered to remove variants with allele frequencies l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The clinical presentation of SARS-CoV-2 infection is highly variable, ranging from asymptomatic infection to severe disease with respiratory failure, overactive immune response, and death occurring in about 0.5%–1% of infections ( Salzberger et al, 2021 ). Known risk factors for severe disease course include demographic characteristics (male sex, older age, and ancestry) and chronic diseases such as obesity, as well as cardiovascular, renal, and respiratory disease ( Yang et al, 2020 ; O'Driscoll et al, 2021 ; Sokologorskiy et al, 2022 ), but these factors do not fully explain differences in clinical severity ( Duman et al, 2022 ; Nhung et al, 2022 ; Petersen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation of SARS-CoV-2 infection is highly variable, ranging from asymptomatic infection to severe disease with respiratory failure, overactive immune response, and death occurring in about 0.5%–1% of infections ( Salzberger et al, 2021 ). Known risk factors for severe disease course include demographic characteristics (male sex, older age, and ancestry) and chronic diseases such as obesity, as well as cardiovascular, renal, and respiratory disease ( Yang et al, 2020 ; O'Driscoll et al, 2021 ; Sokologorskiy et al, 2022 ), but these factors do not fully explain differences in clinical severity ( Duman et al, 2022 ; Nhung et al, 2022 ; Petersen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors from Turkey, Iraq, and Slovenia found no association between the rs2285666 polymorphism and the severity of COVID-19 (Duman et al, 2022;Mahmood et al, 2022;Jevnikar et al, 2022). However, Mahmood et al (2022) reported that the A allele was more commonly detected in the women's case group compared to the control group.…”
Section: Discussionmentioning
confidence: 98%
“…In another study from Turkey, the changes in the ACE2 gene were evaluated retrospectively, and 2 nonsynonymous variants were observed. However, the relationship between these variants and COVID-19 disease could not be established (Duman et al 2022). These two nonsynonymous variants (p.Lys26Arg and p.Asn720Asp) in the ACE2 gene were not detected in our study.…”
Section: Sars-covmentioning
confidence: 99%